2015
DOI: 10.1017/s0022029914000703
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of water soluble extracts and some characteristics of white cheese during the ripening period as effected by packaging type and probiotic adjunct cultures

Abstract: In this study, the chemical composition, proteolysis and in vitro angiotensin-converting enzyme-(ACE)-inhibitory and antioxidant activities of white cheeses made using probiotic adjunct cultures (Bifidobacterium bifidum DSMZ 20456 and Lactobacillus acidophilus DSMZ 20079) were investigated. The cheeses were ripened in a vacuum package or brine for 120 d at 4 °C. The cheese samples maintained the probiotic characteristics of the viable cells as >106 cfu/g even after ripening for 120 d. The proteolysis degrees i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 37 publications
4
14
0
2
Order By: Relevance
“…(2017) study, it was reported that yeasts/molds are associated with traditional dairy products such as butter (Wei et al., 2017). In agreement with this study, Erkaya and Sengul (2015) showed that the mold-yeast counts of TB detectably differed depending on the storage time. In the current study the yeasts/molds count increased eventually in all samples during storage.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…(2017) study, it was reported that yeasts/molds are associated with traditional dairy products such as butter (Wei et al., 2017). In agreement with this study, Erkaya and Sengul (2015) showed that the mold-yeast counts of TB detectably differed depending on the storage time. In the current study the yeasts/molds count increased eventually in all samples during storage.…”
Section: Resultssupporting
confidence: 91%
“…(2014). A free fatty acid value of fresh butter which is between 0.14 to 39% is generally assumed to be passable for butter fat; a higher content of free fatty acid is related to poor storage condition (Nadeem et al., 2013; Erkaya and Sengul, 2015). In the present study all treated samples were in this level on 0 day (0.25, 0.32, 0.29, 0.3, 0.26 and 0.26 in the control, WHE 0.5%, WHE 0.1%, WHE 0.5%, BHT and tocopherol, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…In the same studies, it was found that the change in antioxidant activity was similar to the water‐soluble nitrogen ratio values. Similar results were obtained in the study conducted by Erkaya and Şengül (2015) and Kocak, Sanli, Anli, and Hayaloglu (2020) in white cheese.…”
Section: Resultssupporting
confidence: 90%
“…The release of antioxidant peptides mainly occurs during ripening (Barac et al, 2016;Erkaya & Şengul, 2015;Gupta, Mann, Kumar, & Sangwan, 2009;. Several proteolytic agents can be involved in the formation of peptides such as the coagulant, milk enzymes, enzymes produced by starter, non-starter and secondary cultures, and exogenous enzymes.…”
Section: Strategies Applied To Promote the Release Of Antioxidant Pepmentioning
confidence: 99%